The Democratic Theory of Michael Oakeshott : Discourse, Contingency, and 'The Politics of Conversation'. - Minch, Michael (British Idealist Studies Series 1: Oakeshott, 11., 2012)
His book offers a description, explanation, and evaluation of Michael Oakeshott's democratic theory. He was not a democratic theorist as such, but as a twentieth-century English political theorist for whom liberal theory held deep importance, his thought often engaged democratic theory implicitly, and many times did so explicitly. The author's project penetrates two renewals. The first is the revitalization of interest in Oakeshott, and the second is the renewal of democratic theory which be ...